Effect of existing deposit facilities on the quality of bank liquidity: Applied research in the Central Bank of Iraq for the period (2010 - 2017) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims at showing the effectiveness of the existing deposit facilities in the liquidity of the Iraqi banking system for the period 2010/2017. The problem of research indicates that the Iraqi banking system enjoys high liquidity levels exceeding the standard rate set by the Central Bank of Iraq amounting to 30% For an appropriate level of liquidity remains a major challenge to the management of the bank because it is a trade-off between profitability and liquidity, and also indicates the existence of funds disabled and not available for credit and investment opportunities, and based on the research hypothesis:The existence of a significant effect of the deposit facilities existing in the liquidity of the Iraqi banking system during the period (2010/2017) and using the standard quantitative approach proved that there is a significant effect of the existing deposit facilities in the liquidity of the Iraqi banking system during the period (2010/2017), which came in accordance with economic logic. The study reached a number of conclusions, the most important of which is that the Central Bank has adopted the existing facilities as a tool to control the liquidity of banking and reduce inflation, and recommended the study to continue the work of the existing facility to withdraw the liquidity from banks for two reasons, first is the investment of banks to excess liquidity under The second reason is to control the money supply according to the economic cycles of the country.